Cradle and Developmental Dysplasia of the Hip The tradition and the adverse effect - khorsheed, Dr. Las Jamal (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and Objectives: Landek (Cradle) is a special equipment use for swaddling and calming newborn babies The effect of Landek on the developmental dysplasia of hip has been studied in this research in order to raise the social and cultural awareness about this issue. Methods: 168 cases with developmental dysplasia of hip have been prospectively collected over three years in Duhok-Iraqi Kurdistan. The cases were divided in to two groups. The first group was advised not to use Landek and the other group were continued to use Landek. Both groups are followed up for six months. The grading of DDH was performed depending on the ultrasonic examination (Graf technique). The cases in both groups were diagnosed to have grade IIb. Results: The first group has shown 90% improvement from grade IIb to grade I, 8% to grade IIa and 2% were not improved. The control group has shown deterioration to grade III in 50% of them and to grade IIc in 25%. The rest did not show changes in grade. For the acetabulum to grow properly, it requires a normally positioned femoral head. The popular use of Landek and other swaddling methods among eastern societies were considered to be post-natal risks for DDH because they put hip joint in both adduction and extention position. These two positions were found to be unfavorable for the normal development of hip joint. Conclusions: Landek found to have adverse effect and facilitates the developmental dysplasia of the hip in patents with poorly developed hip joint. Therefore, a broad campaign is necessary against the use of Landek for newborn babies.